The Mediating Role of Organizational Justice Components in the Relationship between Leadership Styles and Job Satisfaction (Global Journal of Management and Business Research, 2012)
The main purpose of this study is to examine the relationship between leadership styles, organizational justice and job satisfaction. Studying this relationship is limited. Therefore, this study focuses on the relationship between leadership styles, organizational justice and job satisfaction in industrial firms in Amman - Jordan. A total of 150 questionnaires have been sent out to the managerial staff in the selected industrial companies. Participants in the study consisted of middle and senior management staff of Sahab Industrial City in Amman- Jordan. The results showed that the transformational leadership and job satisfaction are negatively associated and also there is a positive relationship between transactional leadership and job satisfaction. The distributive justice has a positive correlation with job satisfaction, procedural justice has a negative correlation with job satisfaction, and interactional justice is the only has ab significant and positive relationship with job satisfaction.
Keywords: leadership styles; organizational justice; job satisfaction